Music Preferences of Undergraduate Students in a Multi-Musical Country - Yeoh, Miranda Poh Khoon (1999)
The purpose of the study was to examine the relationships between music preference and each of the four independent variables music characteristics, social influence factors, musical training and familiarity with the music. Ten excerpts of each of the three types of music Commercial, Western Art and Malaysian were recorded on a CD. This is the first instance when a CD, rather than a cassette, is used to contain the sound stimulus. It is also a pioneer work in which preferences for Malaysian Music is studied alongside preferences towards Commercial and Art Music, hence Malaysian genre preferences are discussed in greater detail. Music characteristics, social influences, musical training and familiarity were variables that have been identified in the literature review. Music characteristics included tempo, rhythmic clarity, dynamics, melodic smoothness, pitch, harmony, timbre and mood. Preferences are analysed separately for each of the types of music, since Western Music and Malaysian Music do not share many common characteristics. The social influence variables were influences from family, peers, teachers and media. Musical training was considered as general, overall training in music as well as training for acquiring instrumental skills. Preferences were indicated on a seven-point scale. Familiarity was shown on a three-point scale. The respondents were 171 undergraduates, randomly selected from a local university. Subjects listened to the CD containing the music excerpts and indicated their preferences and familiarity. They also provided demographic data and information concerning their social environment and musical training. The subjects were unpaid. The results showed that all the four independent variables had a bearing upon music preferences. Of the four, familiarity with the music and music characteristics were the most significant correlates for each type of music, although the other two variables also affected music preference significantly. Respondents indicated that the influence of media and peers were higher than the influence of family and teachers, but it was the influence of family and teachers that actually correlated with preference for Commercial and Western Art Music, but not Malaysian Music. Musical training had the highest positive correlation with preference for Western Art Music, among the three types of music. Familiarity and musical characteristics were the correlates that contributed to preference for all the three types of music.